IMPLEMENTASI KEBIJAKAN PEMBEBASAN TANAH UNTUK PELEBARAN JALAN DI KOTA PONTIANAK (STUDI KASUS PEMBEBASAN TANAH DI JALAN PROF. M. YAMIN) - Munawir Munawir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
The purpose of this study is to determine what obstacles or obstacles in the process of road widening at Jln Prof. M. Yamin and the efforts made to overcome it. In this study, researchers used a descriptive type, namely explaining phenomena in depth through data collection. Descriptive research is the steps to re-interpret objects about the state of social phenomena contained in the problem under study. The descriptive method the researcher uses to describe or describe how the form of